2017
DOI: 10.1159/000487048
|View full text |Cite
|
Sign up to set email alerts
|

Elevated HPV16 E1 Expression Is Associated with Cervical Cancer Progression

Abstract: Objectives: The primary replication protein, HPV E1, has been shown to play a role in mitigating host defence and disrupting normal cell cycle processes, leading to the development of cancer. This study investigated the expression profile of HPV16 E1 in various stages of cervical cancer development and the factors that control E1 expression. Methods: One hundred and twenty-four HPV16-positive cervical samples ranging from normal to CIN 1, CIN 2/3, and SCC lesions were studied. E1 mRNA expression was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Among the processes associated with the development of cancer induced by HPV, viral persistence represents a leading key event at the beginning of this process 42 . Recently it was determined that E1 is expressed throughout the different stages of cervical cancer 43 . The authors analyzed the levels of HPV16 E1 mRNA in biopsies with different lesion degrees (CIN) as well as in cervical cancer, observing an increased expression of E1 as long as the lesion advances.…”
Section: Discussionmentioning
confidence: 99%
“…Among the processes associated with the development of cancer induced by HPV, viral persistence represents a leading key event at the beginning of this process 42 . Recently it was determined that E1 is expressed throughout the different stages of cervical cancer 43 . The authors analyzed the levels of HPV16 E1 mRNA in biopsies with different lesion degrees (CIN) as well as in cervical cancer, observing an increased expression of E1 as long as the lesion advances.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous research considered E6 and E7 proteins are targets for immunotherapy against tumors induced by HPV [ 17 ], but the immune response to HPV E1 antigen protein was not reported. Another study also showed the E1 expression can be detected at various stages of CC development where the level was associated with CC prognosis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported hypomethylation of HPV16 early promoter in cervical carcinoma or so-called progressive hypomethylation [23, 24]. Other studies reported hypermethylation of early promoter in cervical carcinoma or progressive hypermethylation [21, 25, 26, 30, 44]. The physical state and copy number of integrated HPV16 genomes were the main reasons of these methylation differences as shown in CaSki and SiHa cells.…”
Section: Discussionmentioning
confidence: 99%
“…The methylation pattern in early promoter especially HPV16 E2BS has been widely studied in cervical cells and the methylation patterns were reported either progressive hypomethylation [23, 24] and progressive hypermethylation [21, 25, 26]. One study showed that high methylation of E2BS was correlated with episomal form in high grade cervical lesions, cervical carcinoma and multiple copies of integrated HPV genome [27].…”
Section: Introductionmentioning
confidence: 99%